Similarities and differences of serotonin and its precursors in their interactions with model membranes studied by molecular dynamics simulation - Wood, Irene (2013)
In this work, we report a molecular dynamics (MD) simulations study of relevant biological molecules as serotonin (neutral and protonated) and its precursors, tryptophan and 5-hydroxy-tryptophan, in a fully hydrated bilayer of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidyl-choline (POPC). The simulations were carried out at the fluid lamellar phase of POPC at constant pressure and temperature conditions. Two guest molecules of each type were initially placed at the water phase. We have analyzed, the main localization, preferential orientation and specific interactions of the guest molecules within the bilayer. During the simulation run, the four molecules were preferentially found at the water-lipid interphase. We found that the interactions that stabilized the systems are essentially hydrogen bonds, salt bridges and cation-π. None of the guest molecules have access to the hydrophobic region of the bilayer. Besides, zwitterionic molecules have access to the water phase, while protonated serotonin is anchored in the interphase. Even taking into account that these simulations were done using a model membrane, our results suggest that the studied molecules could not cross the blood brain barrier by diffusion. These results are in good agreement with works that show that serotonin and Trp do not cross the BBB by simple diffusion.